(untitled) (Public Sector Economics - submission site, 2022)
The main goal of this policy paper is to provide an overview of the basic problems that have impact on healthcare in Croatia and tend to make it unsustainable. The paper points out that the COVID-19 crisis has deepened and exacerbated the already existing problems of financing the health system. The analysis shows that Croatia swept under the rug systemic problems in financing healthcare and ultimately paid the price through frequent financial bailouts. Thus, in the period from 1994-2021, a total of HRK 23.9 billion was spent on bailing out the health service. On the other hand, the COVID-19 crisis can be seen as a chance to start solving the problem and implement certain reforms, both on the revenue and expenditure side of the health system.